CAE ANALYSIS ON WEIGHT OPTIMIZATION IN STEERING KNUCKLE USING ALUMINIUM ALLOY - Sushant Karri, Datla Lohith Varma, Prudhvi Nandan Patchipala, Sarojini Jajimoggalaa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, the research have been focused on the optimization of vehicle especially trends in reducing the weight of various components of a vehicle for better performance is growing wide to reduce the weight is based on reducing weight of steering knuckle. Reducing weight can decrease the safety of vehicle and the parts tend to fail quickly ,though increasing the weight of components could decrease performance as it consumes more fuel due to more weight .The Optimised weight must be chosen and has to be manufactured . The study for optimisation of knuckle is majorly divided int two phases , the first is modeling and primary analysis and the second phase is reducing mass by removing the mass in regions are induced stresses are minimum The silicon carbide reinforced Aluminium 7075 is used for the preparation of a composite using the magnesum powder. The ANSYS workbench was used to conduct a static structural study of the steering knuckle of Al- 10% SiC-1% wt Mg. Compared with results of the Cast iron steering knuckle, which were made from the hybrid MMC with improved construction, the real case loading cases operating under dynamic conditions .The change in material brings a lot of change in the weight of the part. This research focuses on weight optimization uing the Aluminum Grade 7075 & analysis considered with Aluminium 6061 T achieved better performance in reducing weight upto 2700 kg/m3 during the analysis and increase the fuel and steering effeciency.